Warm Ginger and Lemongrass Compress Reduces Joint Pain in Hyperuricemia - Dior Manta Tambunan; Harsudianto Silaen; Rustianna Tumanggor; Martha Sutriska Sagala; Angelina F. Hibur; Agus Nurvianus Zebua; Esti P. S. Harefa; Imelda A. Telaumbanua; Lesi K. H. Gea; Lisbeth F. Sinaga; Sadarman Zendrato; Shara Audi Denada; Yasinta Y. S. Gulo (CV. AFDIFAL MAJU BERKAH, 2026)
The increasing prevalence of gout has led to many health problems and it needs awareness to improve health. One way is providing complementary treatment such as Warm Ginger and Lemongrass Compresses on Reducing Joint Pain in Hyperuricemia Patients. This activity was carried out by lecturer with students from the Nurse Profession Study Program, Murni Teguh University at the Suka Mulia Hulu Village Hall and attended by 21 persons who have Hyperuricemia. The respondents were enthusiastic joining the program and evidently active in Question & Answer session. All respondents were female (100%). Mostly were aged of 56 – 60 years (33.3%), and 51 – 55 years (28.6%). The education levels were mostly Senior High School/Vocational (38.1%), and Junior High School (33.3%). The all respondents were farmer (100%). The majority were not control routinely (57.1%). The majority of respondents were not compliance taking gout medication (61.9%).